Os mares revoltos de luta, resistência e beleza: a arte na transformação do silêncio em linguagem e ação dos corpos gays com deficiência - Yamaguti, Emerson Takumi (2022)
The sea forms a border zone and, in the chanting of Yemanja, all subalternized bodies are embraced, as well as their resistances and struggles. The attempts of the LGBTQIA+ disabled bodies to survive in a Eurocentric, heteronormative, racist, and sexist society. These are historically marginalized, silenced groups that, through social movements, against hegemonic thinking and in favor of the re-signification of identities, of race, gender, class, or sexual orientation, offer voice and visibility to subjects that are considered to be minority groups. The place of speech and the theater as a social location of these groups for their narratives, subjectivities, and dialogues with the dominant class are central axes of this research. The present study aims to analyze and understand how it is possible for LGBT people with disabilities to transform silence into language and action through theater. The tool to carry out the data collection is the Oral History method in the oral life history modality and the background that dialogues and grounds the understanding of decoloniality of LGBT bodies with disabilities and provokes a reflection on the human condition and the relationships that are established in a broad system, is grounded in feminist studies (decolonial and intersectional). The participants of the study are two gay adults with disabilities involved in activities focused on theater and culture in general. Thus, with this study we hoped to analyze theater as a tool that offers driving force for the voices of LGBT people with disabilities to be heard and represented; collaborate to understand the hegemonic process of silencing through which these groups have been submitted; and understand the process of construction of subjectivities, the formation of narratives, and the transformation of pains into language and action through theater. The results obtained through the analysis of the interviews were that art, in this case dance and theater, provide the possibility of developing dialogues for the formation of a network of counter-hegemonic discourses, the formation of social identity, and aid in the elaboration of issues involving sexuality and the acceptance of the body with disability. Contradictorily, in these spaces it was observed the presence of prejudiced attitudes and intolerance, making these environments not welcoming.